1994
DOI: 10.1111/j.2042-7158.1994.tb03812.x
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of Nifurtimox and Metabolite Activity Against Trypanosoma cruzi using Rat Isolated Perfused Liver

Abstract: Nifurtimox disposition was investigated using the rat isolated perfused-liver method after administration of 25 micrograms mL-1 nifurtimox, and its disappearance was monitored by analysing the perfusate sample at various times. Biliary excretion was also measured. The drug concentration profile underwent a biexponential decline over the 2-h study period, with a terminal half-life of 62.76 +/- 17.56 min. Nifurtimox is a high clearance compound (15.23 +/- 5.53 mL min-1). The extraction ratio was 0.621 +/- 0.159.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…A more recent ex vivo study, in which rat livers were perfused in recirculation mode with a solution of nifurtimox, demonstrated that almost no parent compound remained after a 2 h incubation period and that some highly polar metabolites had accumulated. Another notable finding in this study was that samples of perfusate over time retained most of the antiparasitic activity, 10 possibly suggesting the formation of a pharmacologically active metabolite.…”
Section: Introductionmentioning
confidence: 60%
“…A more recent ex vivo study, in which rat livers were perfused in recirculation mode with a solution of nifurtimox, demonstrated that almost no parent compound remained after a 2 h incubation period and that some highly polar metabolites had accumulated. Another notable finding in this study was that samples of perfusate over time retained most of the antiparasitic activity, 10 possibly suggesting the formation of a pharmacologically active metabolite.…”
Section: Introductionmentioning
confidence: 60%
“…[86] Limited human data on NF metabolism, is primarily based on animal trials and proposed metabolites. [87][88] Human CYP isoforms and related enzymes involved in biotransformation remain unidentified, despite animal research suggesting their role. [87,89] NF's 50 % plasma protein binding is not expected to significantly impact drug interactions.…”
Section: Nifurtimoxmentioning
confidence: 99%
“…Under fed conditions, the time to reach C max (T max ) was 4 hours with a high‐fat meal causing a 68 % increase in C max , a 71 % increase in AUC, and a 1‐hour delay in T max. [86] Limited human data on NF metabolism, is primarily based on animal trials and proposed metabolites [87–88] . Human CYP isoforms and related enzymes involved in biotransformation remain unidentified, despite animal research suggesting their role [87,89] .…”
Section: Treatmentmentioning
confidence: 99%
“…Interestingly, in this study Cmax increased 68%, AUC increased 71%, and Tmax increased by 1 hour after a high-fat meal compared to fasted conditions. 96 Animal liver experiments of NF metabolism have suggested a number of metabolites 97 , but this aspect has only been studied in a limited number of humans, with preliminary confirmation of the metabolites observed in animal experiments and further observation of a range of minor metabolites 98 . Data from animal studies also suggests that CYP enzymes are responsible for NF metabolism, but no human data is publicly available identifying specific CYP isoforms, or associated enzymes, responsible for biotransformation 98,99 .…”
Section: Nifurtimox Clinical Pharmacologymentioning
confidence: 99%